Numerical Analysis of Gurney Flap Impact on NACA 4415 Airfoil Aerodynamics Performance - James Julian; Mirza Fauzan Lukiano; Fitri Wahyuni; Waridho Iskandar; Nely Toding Bunga (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa dan Inovasi, 2024)
Improving airfoil aerodynamic performance is an essential aspect of aerodynamic technology. The use of passive flow control is one way to enhance the aerodynamic performance of the airfoil. The influence of using gurney flaps as passive flow control was explored through the CFD approach employing the RANS control equations with the k-epsilon turbulence model. The airfoil model utilized in this investigation was the NACA 4415 operating at a Reynolds number of 1×106. This study explored three different variations of flap height, namely 0.5%, 1%, and 2% of chord length. The outcomes showed that adding gurney flaps showed quite positive results in increasing the lift and drag performance of NACA 4415. An airfoil with a 0.5%c height flap has an average percentage increase in Cl of 12%, followed by a height flap of 1%c, which is 23%, and a percentage Cl of 37% for a height flap of 2%c. Meanwhile, each variation in height flap affected the increase in Cd. A height flap of 0.5%c increased Cd with an average percentage of 2%, while a height flap of 1%c increased the percentage of Cd by 4% and 6% for a height flap of 2%c. Moreover, visualization of fluid flow with pressure and velocity contours given at AoA 12º to determine the effect on the increase in Cland Cd in NACA 4415.